Features of development of soy in dependence on terms of sowing in the conditions of Left-Bank Forest-Steppe zone of Ukraine - Шевніков, М. Я.; Лотиш, І. І.; Галич, О. П. (Scientific Progress & Innovations, 2015)
Friendliness of shoots, density of plants, ripening evenness, size and quality of harvest depends on the term of sowing of soy. A basic criterion of choice of term of sowing is the persistent warming up of sowing layer of soil. A minimum temperature for the shoots of soy makes about +10 oС on condition of subsequent increase of temperature of soil. Warming up of sowing layer to +12–14 oС provides the friendly germination of seed at presence of moisture. The optimal term of sowing for soy is the first half of May. On such conditions for the receipt of normal shoots it is possible to count on the maximal productivity. Early or late lines of sowing reduces the productivity of seed of soy on 12–14 %.